Factor Analysis of The Digital Transformation Challenges at PT Dharma Agung Wijaya - Febri Rizaldy Ramadhian; Mohammad Riza Sutjipto (Publikasi Indonesia, 2025)
Digital transformation is a significant phenomenon across industries, including the oil palm plantation sector. PT Dharma Agung Wijaya is undergoing a digitalization process to improve operational efficiency and effectiveness. However, this process encounters challenges that must be identified and addressed to achieve optimal results. This study analyzes the challenges in implementing digital transformation at PT Dharma Agung Wijaya, identifying its current status, determining key obstacles, and offering recommendations for corrective actions. The research contributes theoretically to digital transformation studies and provides practical benefits for optimizing the company's digitalization efforts. Adopting a quantitative approach with stratified random sampling, the study involves a population of 478 individuals directly engaged in the digital transformation process, with 379 selected as samples. These participants are distributed across four major digital platforms: OWL Plantation System, Budget Control System, DAW Plantation Mobile, and Weightbridge Ramp System. Data were collected via online questionnaires and validated through reliability tests using SPSS.The findings reveal six main factors that challenge the digital transformation process: digital culture, digitalization, digital technology, digital leadership, digital disruption, and digital skills. Among these, digital culture and digitalization were identified as having the most significant impact on the success of the transformation. This study provides valuable insights for PT Dharma Agung Wijaya and similar organizations to navigate and optimize their digital transformation journey effectively.